Systematic literature review: OCB's role in leadership impact on knowledge sharing - Marthalia, Lia; Tukiran, Martinus (Goodwood Publishing, 2025)
Purpose: This study aims to implement an Internet of Things (IoT)-based monitoring system to optimize photovoltaic (PV) system performance and ensure uninterrupted power supply for critical medical equipment, specifically ventilators and monitors, in the ICU room of RSI Siti Khadijah Palembang. Methodology/approach: This current study used a Systematic Literature Review (SLR) methodology to investigate related literature published between 2010 and 2024, identifying relevant publications through research in academic databases such as Dimensions AI. Results/findings: The results showed that TL, JS, and OC positively influence OCB, which in turn enhances SLB. Nevertheless, this study also revealed deficiencies in earlier studies, particularly concerning the function of OCB as a mediator. Conclusion: This study indicates that TL, JS, and OC can positively affect OCB, which then exerts a favorable influence on KSB. Limitations: The availability of research in specific circumstances presents a limitation to the study. Contribution: This study significantly enhances the understanding of how Organizational Citizenship Behavior (OCB) mediates the relationship between Transformational Leadership (TL), Job Satisfaction (JS), and Organizational Commitment (OC) concerning Knowledge Sharing Behavior (KSB), while also creating opportunities for the development of a more comprehensive model.